Discrete geometry and symmetry : dedicated to Károly Bezdek and Egon Schulte on the occasion of their 60th birthdays /: dedicated to Károly Bezdek and Egon Schulte on the occasion of their 60th birthdays. ([2018]) - Unknown
No abstract available